Enzymatic dyeing of keratinous materials - Tzanov, Tzanko (2003)
Poster apresentado no "Biotrans Olomouc 2003 - 6th International Symposium on Biocatalysis and Biotransformations", em Olomouc, Czech Republic, 2003